46.0k views
5 votes
Substitute (2, 1) into x + 3y = 5 to get ✔ 2 + 3(1) = 5 . Simplify the equation to get . Substitute (2, 1) into y = –x + 3 to get ✔ 1 = –(2) + 3 . Simplify the equation to get .

User Ying Xiao
by
4.4k points

1 Answer

4 votes

Answer:

See explanation

Explanation:

A

x + 3y = 5

(x, y) = (2,1)

x + 3y = 5

2 + 3(1) = 5

2 + 3 = 5

5 = 5

The equation is true

B.

y = –x + 3

(x, y) = (2, 1)

y = –x + 3

1 = -2 + 3

1 = 1

The equation is true

User Rory Daulton
by
5.0k points